Utilization Of Digital Marketing For Palm Oil Farmers And Palm Fruit Craftsmen In Indonesia - Judijanto, Loso; Liestyowati, Liestyowati; Belani, Sri Wanti; Daud, Anshar; Syofya, Heppi (Universitas Pahlawan Tuanku Tambusai, 2024)
When researchers carried out community service in the villages of Lebaksari village, West Java, Lumpoknyo Luwuk Bangai village, Mapalla village Makassar, and Batang Merangin Jambi, researchers discussed with oil palm farmers and palm and coconut frond craftsmen. Oil palm and palm frond farmers in West Java village, Lumpoknyo Luwuk Bangai village, Mapalla village Makassar, and Batang Merangin Jambi farmers and frond craftsmen complained that their businesses had stalled and seemed to be running in place. Then the servant/writer held discussions with colleagues online, consulted with experts and village officials. In the end, the author/devotee based on the results of discussions with stakeholders agreed that the main problems experienced by farmers and frond craftsmen in Lebaksari village, West Java, Lumpoknyo Luwuk Bangai village, Mapalla village Makassar, and Batang Merangin Jambi . The result in this article show that 1). When the community service carried out observations for one month and discussed with local residents, the majority of whom were oil palm farmers and frond craftsmen, they experienced marketing problems. Then researchers found digital marketing solutions. 2). Digital marketing strategies, e-commerce, and websites are one unit that the author believes can overcome the marketing problems experienced by oil palm farmers and frond craftsmen in the villages of West Java village, Lumpoknyo Luwuk Bangai village, Mapalla village Makassar, and Batang Merangin Jambi.